Taphonomic analyses of Conularia quichua (Cnidaria, Conulariidae) from Pimenteira Formation (Middle Devonian), Parnaiba Basin, Tocantins State, Brazil - Sousa, Felipe Nascimento [UNESP]; Dangio, Ana Laura [UNESP]; Ghilardi, Renato Pirani [UNESP] (Soc Brasileira Geologia, 2024)
Conulariids are extinct scyphozoans, have benthic and sessile life modes, and inhabited shallow marine platforms. Taphonomic studies of these animals from the Parna & iacute;ba Basin are scarce, distinctly from the Paran & aacute; Basin. The present work seeks to analyze the taphonomic characteristics of Conularia quichua from the Pimenteira Formation, Parna & iacute;ba Basin, and infer deposition events that influenced this fossiliferous concentration. The material is housed at Laborat & oacute;rio de Paleontologia de Macroinvertebrados (LAPALMA) and consists of 43 specimens. The taphonomic signatures used in the analyses were orientation in relation to the bedding plane, concentration, degree of preservation, and theca filling. The cluster and correspondence analyses evidenced two taphonomic classes for single-unit, fragile skeletons of conulariids from Pimenteira Formation: the taphonomic class 1 comprehends obliquely, filled, and complete skeletons; the taphonomic class 2 comprehends concordantly, fragmented, flattened, grouped, and isolated skeletons. A high-stand system tract, after the maximum transgressive surface of the Pimenteira Formation, is interpreted to be the depositional environment of this concentration, where an episodic high-energy event was responsible for the fossiliferous lens. In addition, the lack of preserved calcium carbonate shells suggests acidic conditions, assuming that diagenetic control occurred in this accumulation.
Keywords: taphonomic signatures; cluster analysis; correspondence analysis; biostratinomy